The predictors of endoleaks after endovascular repair of experimentally produced fusiform carotid aneurysm in canine. Issue 2 (3rd March 2016) - Shi, Wan-Yin; Gu, Jian-Ping; Li, Ming-Hua; Yan, Lei; He, Xu
Abstract: Objective: Endoleaks constitute the main concern regarding the use of covered stents in the treatment of intracranial aneurysms. We investigated immediate/late endoleaks after stent-graft placement for the treatment of experimentally created carotid fusiform aneurysm (FA) in a canine model.Material and methods: Eighteen carotid FAs in nine dogs receiving covered stents were followed. Their procedural and angiographic data were collected immediately and six months after stenting. Univariate analysis and multivariate logistic regression analysis were performed to determine the factors predictive of immediate/late endoleaks. Receiver operating characteristic curve analysis was performed to determine the best cutoff values of the independent factors.Results: All carotid FAs were successfully treated with Willis covered stents and received a six-month follow-up. The rate of immediate and late endoleaks after stenting was 38.89% and 16.67%, respectively. Anchoring length was identified as independent predictor of immediate endoleaks ( P =0.037 ) and its best cutoff value was 3.06mm (95% confidence interval: 2.39-3.72). No parameters were identified to be independent predictors of late endoleaks.Conclusions: Treating carotid FAs with Willis covered stents is technically feasible. Most endoleaks heal spontaneously and significantly correlate with anchoring length.